2023
DOI: 10.1007/s11356-023-25407-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of government governance and environmental taxes on sustainable energy transition in China: fresh evidence using a novel QARDL approach

Abstract: Although economies have experienced immense growth in recent times, however, it also comes with environmental and social consequences which question the current practices and threaten the well-being of current as well as the future generation. This realization, thus, pushes institutions to bring change in existing energy-related policies in order to incorporate social and environmental concerns. Clean energy transition, in this regard, is gaining attraction all over the world as it shifts away economies from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…This involves expanding energy access in rural and remote areas, often through decentralized renewable energy systems, and implementing programs to improve energy affordability and reduce energy poverty. Socially inclusive energy policies also focus on public engagement and participation in energy decision-making processes, ensuring that the benefits of energy transition are widely shared and that the interests and rights of all stakeholders, including indigenous peoples and local communities, are respected and protected [133][134][135] . The relationship between sustainability and energy policies necessitates an integrated and collaborative approach transcending sectoral and disciplinary boundaries.…”
Section: Sustainability and Marketing In The Energy Sectormentioning
confidence: 99%
“…This involves expanding energy access in rural and remote areas, often through decentralized renewable energy systems, and implementing programs to improve energy affordability and reduce energy poverty. Socially inclusive energy policies also focus on public engagement and participation in energy decision-making processes, ensuring that the benefits of energy transition are widely shared and that the interests and rights of all stakeholders, including indigenous peoples and local communities, are respected and protected [133][134][135] . The relationship between sustainability and energy policies necessitates an integrated and collaborative approach transcending sectoral and disciplinary boundaries.…”
Section: Sustainability and Marketing In The Energy Sectormentioning
confidence: 99%
“…Among the four hypotheses mentioned above, the second-most applied is the feedback hypothesis [48,72,84], with a total of five research articles. This hypothesis posits a bidirectional causal relationship between energy use and economic development, suggesting that energy use and economic growth mutually influence and promote each other [25].…”
Section: Growth/feedback/neutrality/conservation Hypothesismentioning
confidence: 99%
“…Additionally, continuous energy transition, increasing the share of renewable energy or enhancing energy efficiency, is not expected to have negative impacts on economic development. Studies found that economic growth only affects clean energy transition in very high quantiles (0.60-0.95) [84]. On the other hand, research in [48] indicated that energy demand does not have a feedback effect on economic growth.…”
Section: Growth/feedback/neutrality/conservation Hypothesismentioning
confidence: 99%
See 2 more Smart Citations